Podatkowe narzędzia wspierające rozwój małych przedsiębiorstw - Żabiński, Arkadiusz (Tax instruments to support small business development, 2006)
The article discusses the use of tax instruments for supporting the development of small business. The analysis covers personal income tax addressed at the self-employed. The tax can be payable as a fixed amount tax, fiat rate tax, or on general principles. The structural elements of personal income tax are analyzed in the context of their use for supporting the development of small business. The author also evaluates governmental initiatives in this field.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 170-179